The Potential Of Adult Men’s Entertainment Business, Its Impact On Economic Development, Creative Economy, And Human Development, Through Lifestyle And Positive-Negative Chain Effects For Communities In The Capital City Of Nusantara ( IKN ) Area & City - Diah Riyani; Hwihanus Hwihanus; Muhammad Bayu; Darmono Darmono (International Journal of Economics, Business and Innovation Research, 2023)
This article was written with the aim of describing the potential impact of the adult male entertainment business on economic development, human development, the creative economy through lifestyle, as well as the negative and positive effects of the entertainment business. This research is a literature review and research model of actual problems that exist in today's society. The approach used in this research is qualitative, while the type of research used is library research. Entertainment is a form of activity that provides amusement and holds the interest and attention of an audience. The entertainment industry is a multi-faceted combination, or a group of sub-industries, of a wide spectrum of media, such as music, print media, television, amusement parks, gaming, gambling, sports, fine arts, toys, movies, and other forms of entertainment people have grown to do during their leisure time. Entertainment as an industry has developed due to leisure being a determining factor in recreation development. Although business entertainment is a popular social practice worldwide, there are also wide variations in its popularity and legitimacy in different countries. China and Japan, for example, both legitimize entertainment expenses as an accounting item for tax returns. According to the annual reports of more than 200 companies listed on the Shanghai Stock Exchange, these companies spent more than 10 percent of their net profit on business entertainment in 2007 (Shanghai Stock Exchange, 2009). In 2008 alone, entertainment expenses for Japanese companies amounted to US$32 billion (National Tax Agency of Japan, 2012). Business entertainment, although still observable in the US, is practiced on a much smaller level or scale than is seen in Asia.